(untitled) (Research, Society and Development, 2023)
This paper seeks to identify publications in the literature that indicate the use of RCA as a methodology for event management in the Emergency Department and its contributions to the care team through a Systematic Literature Review. Data collection was done through a virtual search of articles and studies indexed in the Virtual Health Library (VHL), Cochrane, Elsevier and Brazilian Digital Library of Theses and Dissertations (BDTD) databases. As a result, 17 studies were found, which were treated through Content Analysis, distributed in three categories, namely: Use of the ACR in the Emergency Department, Recommendations and Limitations of the use of the ACR - a critical analysis and Use of other tools for the Management of Adverse Events in the Emergency Department. It is concluded that, despite not being fully utilised in some ED settings, RCA remains the tool of choice for root cause analysis of adverse events. The present study points to the possibility of associating the DMAIC methodology to the use of the tool with a view to reducing the turnaround time of the analysis, the implementation of improvements and the monitoring of results.